2016
DOI: 10.1111/mpp.12347
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved metalloprotease effector enhances virulence in the maize anthracnose fungus Colletotrichum graminicola

Abstract: Colletotrichum graminicola causes maize anthracnose, an agronomically important disease with a worldwide distribution. We have identified a fungalysin metalloprotease (Cgfl) with a role in virulence. Transcriptional profiling experiments and live cell imaging show that Cgfl is specifically expressed during the biotrophic stage of infection. To determine whether Cgfl has a role in virulence, we obtained null mutants lacking Cgfl and performed pathogenicity and live microscopy assays. The appressorium morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 64 publications
3
78
0
Order By: Relevance
“…In vitro chitinase activity assays of leaves infected with wild-type and null mutant strains show that, in the absence of Cgfl, maize leaves exhibit increased chitinase activity. Similarity searches, phylogenetic analysis, and transcriptional profiling revealed that C. graminicola encodes two LysM domain-containing homologs of Ecp6, suggesting that this fungus employs both Cgfl-mediated and LysM protein-mediated strategies to control chitin signalling (Sanz-Martín et al 2016). …”
Section: Fungal Potential Against Host Immune Systemmentioning
confidence: 99%
“…In vitro chitinase activity assays of leaves infected with wild-type and null mutant strains show that, in the absence of Cgfl, maize leaves exhibit increased chitinase activity. Similarity searches, phylogenetic analysis, and transcriptional profiling revealed that C. graminicola encodes two LysM domain-containing homologs of Ecp6, suggesting that this fungus employs both Cgfl-mediated and LysM protein-mediated strategies to control chitin signalling (Sanz-Martín et al 2016). …”
Section: Fungal Potential Against Host Immune Systemmentioning
confidence: 99%
“…Significant virulence reduction in the SG200∆umfly1 mutant also confirms the relevance of fungalysin in the U. maydis –maize interaction. Consistently, cgfl of C. graminicola was also found to be involved in virulence during maize infection (Sanz‐Martin et al ., ). The observed reduction of ZmChiA cleavage activity, as well as the reduced virulence both in the SG200∆umfly1 mutant and the active site mutant (SG200∆umfly1‐C mut ), indicates that the enzymatic activity of UmFly1 is required for the cleavage of maize ZmChiA, and consequently for U. maydis virulence.…”
Section: Discussionmentioning
confidence: 97%
“…Contrarily, in U. maydis , the deletion of umfly1 alone already results in a loss of ZmChiA cleavage activity and a reduced virulence of the fungus, indicating the importance of umfly1 for interaction with the host plant. Consistent with these results, cgfl of C. graminicola is also involved in virulence during maize infection (Sanz‐Martin et al ., ). Additionally, U. maydis also contains a single‐copy gene orthologous to fosep1 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations